EVALUASI FORMULASI SEDIAAN MIKROENKAPSULASI EKSTRAK ETANOL DAUN MINDI (Melia Azedarach L.) - Casey Dola Rebeca br Pinem; Razoki Razoki; Erida Novriani (JIFI (Jurnal Ilmiah Farmasi Imelda), 2026)
Microencapsulation is a technology used to protect active ingredients from environmental influences and enhance their stability. This study aimed to evaluate the formulation of microencapsulated ethanol extract of mindi leaves (Melia azedarach L.), which possesses pharmacological activities as an antioxidant, antibacterial, and antidiabetic agent. The extraction of mindi leaves was performed using the maceration method with 80% ethanol, yielding a 10.4% extract. Microencapsulation was prepared using sodium alginate and chitosan as coating materials, with three different extract concentrations (0.25%, 0.5%, and 0.75%). Formulation evaluation included moisture content testing, stability testing using cycling test, and floating test on rat gastric mucosa. The results showed that moisture content ranged from 0.37% to 0.63%, with the 0.75% formulation having the lowest moisture content (0.37%). Stability testing over six cycles demonstrated that all formulations remained stable without significant changes in color, texture, and shape. The floating test showed a lag time of less than 2 minutes for all formulations with floating time ranging from 3 to 6 hours, where the 0.25% concentration exhibited the longest floating time (6 hours). It can be concluded that microencapsulation technology successfully produced mindi leaf ethanol extract preparations with stable characteristics, low moisture content, and good floating capability, making it potential as an oral drug delivery system.